Memberdayakan Siswa SMK melalui Pelatihan Kewirausahaan dan Desain Produk: Pelibatan Masyarakat di SMK Terpadu Husnul Hidayah Mojokerto - Budiyono Santoso (Karawo : Journal of Community Service (KJCS), 2024)
Entrepreneurship and product design training is a strategic approach to foster creativity, innovation, and independence among vocational students. This community service activity aimed to introduce basic concepts of entrepreneurship, product idea development, and creative thinking to students at SMK Terpadu Husnul Hidayah Gondang Mojokerto. The implementation methods included initial observation, lecture presentations, discussions, and evaluation through pre- and post-training questionnaires. Results indicated that 92% of participants experienced an increase in understanding of entrepreneurship and product design. The training was considered highly beneficial by 84% of participants, while 79% appreciated the interactive learning process. This activity demonstrates that integrating entrepreneurial education into vocational schools can enhance student readiness for the challenges of the business world.